A Comprehensive Review on the Anti-inflammatory Activity of Chalconesderived Moieties - Mittal, Roopal; Sharma, Shailesh; Kushwah, Ajay S.; Yaqoob, Obaid; Kumari, Deepika (Current Traditional Medicine, 2024)
Background: In recent decades, all-embracing research accounting for thousands of natural bioactive compounds have been detailed on behalf of their origin, pharmacological activity, active phytoconstituents, and therapeutic applications. Chalcones, secondary metabolites have shown therapeutic potential against various forms of inflammation, pain, and cancer in multiple research papers targeting their pathway inhibition and their significant therapeutic activity. Area Covered: Diverse aspects of chalcones have been focused on with their biological source, pathway inhibition, and pharmacological activity.Objectives: This study aims to focus on the chalcones being the origin of ethnopharmacological, possess extensive pharmacological activities, including anti-neoplastic, antimicrobial, anti-inflammatory, antioxidant, anti-acne, anti-aging, hepatoprotective, neuroprotective, psychoactive, anti-parasitic, and many others.Methods: Chalcones display anti-inflammatory activity via COX-2, NO synthase, and TNF-α inhibition. Furthermore, comprehensive studies will be discussed with a viewpoint of the chalcones's role in the alleviation of inflammation. According to recent advancements, chalcones clinically have been used in the treatment of inflammation, anti-aging, oxidative stress reduction, autophagy, and apoptosis.Conclusion: This article focuses on the molecular progression of inflammation and the chalcone role in combating inflammation by targeting inflammatory mediators and pathways.
Keywords: narigenin